Carl Rogers na educação de ensino médio - Oliveira, Igor Alves Dantas de (2015)
The present research proposes, from an interview conducted with high school students in a regular school, and a literature search on the humanistic approach of Carl Rogers, to discuss the applicability of the author’s theories in high school education. It is introduced, first, the information about the school in which the survey was conducted, as well as the characteristics of the interviewed group. Also, it is presented the “etnopesquisa”, methodology chosen for this work. Hereafter, I perform a study of the humanistic approach of Carl Rogers for Psychology and Education, showing his approach as a counterpoint to B.F. Skinner behaviorism, which also gained strength in the 1970s. Thus, pointing out that the current education model followed by the school, to focus the schooling on examinations for entering college, is not promoting meaningful learning, that is, learning that motivates changes in thinking and behavior in students. The interview analysis shows that students, despite not knowing Carl Rogers and his approach, are looking for an education fairly close to that suggested by the author. From the Rogers approach, it is suggested a more reflective school, centered on the student, where he or she will pass through a self-discovery process and therefor, a meaningful learning experience, having the teacher as a facilitator of this process.